العوامل المؤثرة على إنتاجية العامل في الشركة العامة للخيوط القطنية باللاذقية - بشماني, شكيب (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى تحديد العوامل المؤثرة على إنتاجية العامل في الشركة العامة للخيوط القطنية باللاذقية, وترتيبها حسب أهميتها النسبية. تمّ التوصل إلى النتائج الآتية: - بنتيجة الدراسة جاءت العوامل وفق الترتيب التالي: الحقوق العمالية, نظام الحوافز, المكافآت, التأهيل والتدريب, بيئة العمل المادية, ضغوط العمل, عبء العمل, الترقيات, علاقات العمل. وبما أن المكون الأول له الأكبر من التباينات, لذلك ينبغي التركيز على المكونات المترابطة معه, وأخذها أولوية عند دراسة العوامل المؤثرة على إنتاجية العامل, وهذه العوامل هي: الحقوق العمالية, نظام الحوافز, المكافآت. - وجود علاقة طردية ذات دلالة معنوية بين (الحقوق العمالية, المكافآت, التأهيل والتدريب, بيئة العمل المادية, الترقيات, علاقات العمل) وإنتاجية العامل في الشركة المدروسة. - وجود علاقة عكسية ذات دلالة معنوية بين (ضغوط العمل, عبء العمل) وإنتاجية العامل في الشركة المدروسة. The research aims to identify the factors affecting worker productivity in the General Company for Cotton Yarn in Latakia, arranged according to their relative importance. Reached the following results: - outcome of the study were factors in the following order: labor rights, the system of incentives, rewards, rehabilitation and training, the physical work environment, work stress, workload, promotions, labor relations. As the first component of a bulk of the variations in form before recycling and beyond, so it should focus on the components involved in this component, and take priority when studying factors affecting worker productivity, and these factors are: labor rights, the system of incentives, rewards. - The presence of significant positive relationship between spirits (labor rights, bonuses, rehabilitation and training, the physical work environment, promotions, labor relations) and worker productivity in the company studied. 3- The presence of significant inverse relationship between spirits (work stress, workload) and worker productivity in the company studied.